Religious views on the origin and meaning of COVID-19 - Pieterse, Tanya (HTS teologiese studies, 2021)
For ages, natural disasters, war and disease have been part of life, sharing themes of not only adversity, fear and death, but also hope. The year 2020 brought a new threat in the form of coronavirus disease 2019 (COVID-19), which challenged what humankind understood of all they knew and believed. The significant difference today is the role of the media in sharing news and opinions on this disease that threatens not only lives, but also spiritual well-being. In this study, we focus on people’s religious views on the origin and meaning of this invisible threat to establish how this pandemic impacts on people’s belief systems. The 20th century was marked by a shift whereby actions and events are intellectualised to rationalise cause and effect, and the philosophical theodicies are regarded to limit our critical reasoning. This study, however, shows that COVID-19 reactivates this debate in that it surpasses logic and rational thinking. Data are collected by means of comments, discussions and opinions shared on numerous social media platforms. During times of adversity, the same rhetorical ‘who’ and ‘why’ questions are asked and in this regard, theodicy as a philosophical framework informs this study. Applying a narrative inquiry, data are interpreted and three themes are identified, namely COVID-19 is an act God, COVID-19 has nothing to do with God and God remains in control amidst a devastating pandemic. The sample for this study is random and the medium used allows for representativity in terms of age group (18+), gender, race, religious affiliation of South Africa, but not limited to this country.Contribution: This article provides insight into renewed debates on religious views on pandemics and suffering in the context of COVID-19. It contributes to an understanding of different perceptions on the origin of this disease, how people make sense and find meaning in being part of a global discourse.